ОРОНІМИ В КРАЄЗНАВЧО-ТУРИСТCЬКИХ МАРШРУТАХ - Бучко, Жанна; Бучко, Нестор; Руденко, Валерій (Чернівці, 2010)
An origin, semantic value and informing of oronymes of Ukrainian Carpathians is examined. What information they carry and as she can be used in the regional providing of tourist routes it is shown on numerous material
Oronymes in regional-tourist trails
Oronymes in regional-tourist trails
Keywords: Краєзнавчо-туристський маршрут; Оронім; Оронімія; Топонімія